Fractalkine mediates inflammatory pain through activation of satellite glial cells - Souza, Guilherme R; Talbot, Jhimmy; Lotufo, Celina M; Cunha, Fernando Q; Cunha, Thiago M; Ferreira, Sérgio H (Proceedings of the National Academy of Sciences - PNAS, 2013)
The activation of the satellite glial cells (SGCs) surrounding the dorsal root ganglion (DRG) neurons appears to play a role in pathological pain. We tested the hypothesis that fractalkine, which is constitutively expressed by primary nociceptive neurons, is the link between peripheral inflammation and the activation of SGCs and is thus responsible for the genesis of the inflammatory pain. The injection of carrageenin into the rat hind paw induced a decrease in the mechanical nociceptive threshold (hypernociception), which was associated with an increase in mRNA and GFAP protein expression in the DRG. Both events were inhibited by anti-fractalkine antibody administered directly into the DRG (L5) [intraganglionar (i.gl.)]. The administration of fractalkine into the DRG (L5) produced mechanical hypernociception in a dose-, time-, and CX3C receptor-1 (CX3CR1)-dependent manner. Fractalkine's hypernociceptive effect appears to be indirect, as it was reduced by local treatment with anti-TNF-α antibody, IL-1-receptor antagonist, or indomethacin. Accordingly, the in vitro incubation of isolated and cultured SGC with fractalkine induced the production/release of TNF-α, IL-1β, and prostaglandin E2. Finally, treatment with i.gl. fluorocitrate blocked fractalkine (i.gl.)- and carrageenin (paw)-induced hypernociception. Overall, these results suggest that, during peripheral inflammation, fractalkine is released in the DRG and contributes to the genesis of inflammatory hypernociception. Fractalkine's effect appears to be dependent on the activation of the SGCs, leading to the production of TNFα, IL-1β, and prostanoids, which are likely responsible for the maintenance of inflammatory pain. Thus, these results indicate that the inhibition of fractalkine/CX3CR1 signaling in SGCs may serve as a target to control inflammatory pain.